The instructive role of mechanical properties of polyvinyl alcohol film in the process of YSZ tape calendering. Issue 10 (July 2020) - Zhang, Bowen; Gong, Junyi; Wei, Keyan; Yue, Shuai; Jiang, Cairong; Ma, Jianjun
Abstract: Aqueous tape calendering offers the advantage of a simple fabrication process, inexpensive equipment, and environmental friendliness. Polyvinyl alcohol (PVA), as a polymer, is a conventional binder for aqueous tape calendering. In this innovative work, we aim to achieve a suitable process for tape calendering, by studying mechanical properties of the PVA polymer film with a series of plasticizers. The results show that the elongation at break of the PVA film reaches a maximum of 828.26%, using a triple plasticizer of glycerol, polyethylene glycol (PEG) 200, and PEG 400. With an optimized ratio of the binder to the plasticizer, a YSZ sheet with a relative density of 98% and a conductivity of 0.043 S cm −1 at 800 °C is obtained by sintering at 1400 °C, demonstrating comparable performance to those of the YSZ electrolytes by dry pressing. SEM reveals that the sintered YSZ body is dense, and has no visible open and closed pores. The mechanical properties characterization of the PVA polymer film adopted in this paper has instructive significant instruction for tape calendering and tape casting methods. Highlights: Mechanical properties measurement of the PVA film applied in an aqueous tape calendering. The elongation at break of the PVA film reached 828%. Combination of glycerol, PEG200 and PEG 400 plasticizer is a preferred choice for PVA binder. The YSZ sheet sintered at 1400 °C has a density of more than 98% and a conductivity of 0.043 S cm −1 at 800 °C.